Recent variations of a debris-covered glacier (Brenva glacier) in the Italian Alps monitored by comparison of maps and digital orthophotos - C. D'Agata; C. Smiraglia; A. Zanutta; F. Mancini (International Glaciological Society, 2005)
Debris-covered glaciers are widespread in the mountain chains of Asia (e.g. the Karakoram, the Himalaya and the Tien Shan). They are also particularly common in New Zealand , in the Andes and in Alaska. Despite their relatively common occurrence, debris-covered glaciers have not been well studied. In this contribution the recent evolution of Brenva debris covered glacier is analyzed by aerial photocomparisons. The Brenva glacier tongue exhibited two main phases during the second half of the 20th century: a strong positive pattern of volume and thickness change between 1959 and 1983, and a less strong negative pattern between 1983 and 1999. The first phase may be explained by a drop in summer temperature (between 1951 and 1960 the temperature was 0.658C lower at Courmayeur, close to the glacier, than the 1936–83 mean), accompanied by increased annual precipitation. Earlier Brenva glacier results are comparable with the general trend of the ‘clean’ Italian glaciers (they also registered a phase of positive mass balance), but the recent behaviour of the glacier is very different. In fact, at the end of the 20th century, Brenva glacier and other debris-covered glaciers such as Miage and Belvedere showed a net positive balance because of the debris insulation effect, allowing more ice at the lower tongue of the glacier to be conserved